Mechanical and piezoresistive properties of multi-walled carbon nanotubes reinforced epoxy matrix composites for pipeline monitoring - Pengyang Li; Yangyang Xia; Chao Zhang; Cuixia Wang; Yu Liu; Hongyuan Fang; Fuming Wang (Journal of Materials Research and Technology, 2024)
Pipeline deformation monitoring is of vital importance for pipeline maintenance. However, no durable and effective methods have been seen for deformation monitoring of buried pipes, especially drainage pipes. In this paper, an embedded multi-walled carbon nanotubes (MWCNTs) reinforced epoxy (EP) matrix composite for pipeline monitoring was developed. The bending properties, piezoresistive properties and stability of MWCNTs/EP composites were investigated using three-point bending tests, cyclic tests, resistivity tests, and scanning electron microscope (SEM) observations. The results indicated that when the MWCNTs content was at 0.1 wt%, the bending strength, bending modulus and bending strain increased by 12.3 %, 8.7 % and 25.1 % respectively. The conductive percolation threshold was at 0.7 wt%, and the resistance changed in three stages under bending. In addition, the MWCNTs/EP composites had stable piezoresistive properties under different loading rates and small strain cyclic (ε < 1.5 %). The MWCNTs content and dispersion effect were the main factors affecting the bending properties of MWCNTs/EP composites, while the resistance change mainly originated from the change of the MWCNTs conductive network. This work provided a new idea for pipeline deformation monitoring.